Designing and evaluating of jig for holding cylindrical parts for mass production for drilling operation - Fazlina, Mansor (2010)
The project study is about a designing and evaluating of jig for holding cylindrical parts for mass production of drilling operation. Three design were draw and compared in terms of material and also the strength of the jigs to select the best design. This report begin with an introduction of jigs which is definition and important component in jigs and advantages of the jigs. Drilling jig is used whenever it is necessary to drill hole to exact location. The objective of this study is to design and analyze the drilling jig which can hold 30 work-piece of small cylindrical parts. Design were evaluate in terms of force applied to the jig. Three new jig were designed using SolidWorks software. The design were analyze using FEA tools which is Algor software. Pugh Concept Selection also applied in selection the best design. Material AISI 1040, AISI 1018 and Iron, Fe selected to make analysis and as the result, material AISI 1040 were chosen for the jig. Design also evaluate by using two difference force value which is 400 N and 1000 N to choose the strongest design. The results for force 400 N showed that design 3 have lowest maximum von mises value with 0.5660021 N/mm2 compared to design 1 with 1.066816 N/mm2 and design 2 with 37.70809 N/mm2. Design 3 were selected to be the final design and AISI 1040 selected as the jig material because it strongest compared to AISI 1018 and Iron, Fe.